Slow-release polycarboxylate water-reducing agent for reducing cement consumption of concrete and preparation method thereof
By combining hydrolyzable groups with the nucleation of nano-calcium carbonate and using a staged stirring process, an anti-mud-slow-release synergistic mechanism is constructed, which solves the problem of balancing cement reduction and concrete performance in existing technologies. It achieves a balance between cement reduction and strength stability, and improves the flexibility of process control and the slow-release effect.
Patent Information
- Application Number
- CN202511781837.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-29
- Publication Date
- 2026-06-30
- Estimated Expiration
- 2045-11-29
AI Technical Summary
Existing technologies struggle to significantly reduce cement usage while ensuring concrete workability and strength. Furthermore, the slow-release effect of polycarboxylate superplasticizers is easily diminished in mud-containing aggregate systems, resulting in insufficient flexibility in process control and making it difficult to balance cement reduction with strength assurance.
By employing the nucleation effect of composite hydrolyzable groups (itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, N-hydroxymethylacrylamide) and nano-calcium carbonate, combined with a staged stirring process, an anti-mud-slow-release synergistic mechanism is constructed. Through multi-gradient regulation, the cement hydration process is precisely matched, promoting full hydration of cement particles and enhancing anti-mud performance.
This approach achieves the goal of maintaining the workability and strength stability of concrete while reducing cement usage, broadens the adaptability range of aggregate mud content, enhances the flexibility and compatibility of process control, and solves the technical bottleneck of cement reduction and strength assurance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the fields of concrete engineering and green building materials, and in particular to concrete with slow-release polycarboxylate superplasticizer that reduces cement content and its preparation method. Background Technology
[0002] In the field of concrete engineering, with the promotion of energy conservation, emission reduction, and green building materials concepts, reducing cement usage has become an important development direction for the industry, which can reduce carbon emissions and lower engineering material costs. Polycarboxylate superplasticizers, as high-efficiency concrete admixtures, rely heavily on optimizing their slow-release and anti-mud properties to achieve cement reduction. Currently, most slow-release polycarboxylate superplasticizers achieve slump retention by introducing a single hydrolyzable functional group to ensure concrete workability. To address the impact of aggregate mud content on superplasticizer performance, related technologies often incorporate anti-mud components into the superplasticizer, reducing ineffective consumption by occupying clay adsorption sites or shielding the negative charge of clay. Meanwhile, concrete preparation processes often employ one-time addition or simple staged mixing methods. Some solutions, to enhance slow-release or cement reduction effects, rely on complex molecular structure modification designs or specialized production and mixing equipment. Furthermore, to compensate for potential performance losses due to cement reduction, existing technologies often optimize performance by adjusting the water-cement ratio or adding mineral admixtures, but overall, they still focus on improving a single performance dimension.
[0003] However, existing technologies still have many limitations in practical applications: First, the design of existing slow-release polycarboxylate superplasticizers often focuses on the slow-release function of functional groups in isolation, failing to effectively combine the slow-release mechanism with the enhancement of cement hydration process and the control of mixing technology, making it difficult to achieve a significant reduction in cement content while ensuring concrete workability; Second, the synergistic compatibility between anti-mud components and slow-release components is insufficient, and the two are prone to interaction, resulting in a significant reduction in the slow-release effect of the superplasticizer in mud-containing aggregate systems, and a narrow range of compatibility with aggregates of different mud contents; Third, existing technical solutions for achieving long-term slow-release or cement reduction effects either require complex molecular structure modification or rely on dedicated production or mixing equipment, resulting in poor compatibility with the conventional production conditions of existing concrete batching plants and insufficient flexibility in process control; Fourth, the balance between cement reduction and strength protection has not been effectively resolved. In existing technologies, after reducing cement content, insufficient cement hydration and insufficient generation of hydration products often lead to a significant loss of concrete strength, making it difficult to simultaneously meet the dual requirements of cement reduction and strength stability. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a slow-release polycarboxylate superplasticizer for concrete with reduced cement content and a method for preparing the same, so as to solve one or more problems in the prior art.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] Slow-release polycarboxylate superplasticizer reduces cement usage in concrete:
[0007] By weight, it includes 280-320 parts cement, 650-750 parts sand, 1100-1200 parts stone, 140-160 parts water, and 4-6 parts of slow-release polycarboxylate superplasticizer.
[0008] The concrete is prepared by the following method:
[0009] (1) Preparation of slow-release polycarboxylate superplasticizer mother liquor: By mass, 80-90 parts of polyethylene glycol monomethyl ether, 25-30 parts of acrylic acid, 8-12 parts of itaconic acid monobutyl ester, 5-8 parts of dimethyl carbonate modified acrylate, 3-5 parts of N-hydroxymethylacrylimide, 1.2-1.8 parts of ammonium persulfate, 0.8-1.2 parts of mercaptoacetic acid and 150-180 parts of deionized water are mixed for polymerization reaction.
[0010] (2) Compound water-reducing agent finished product: Based on the mass of the water-reducing agent mother liquor, add 0.5-1 parts by mass of L-aspartic acid dimethyl ester and 0.1-0.3 parts by mass of nano calcium carbonate to the mother liquor obtained in step (1), and mix and disperse evenly.
[0011] (3) Staged mixing: Add 60%-70% water to the mixture of sand and stone and stir for 0-30s. Add all the slow-release polycarboxylate superplasticizer and continue stirring for 30-60s. Then add cement and the remaining 30%-40% water and stir for 60-120s until uniform.
[0012] The sand has a mud content of ≤3%, the stone has a mud content of ≤1%, the water to cement mass ratio is 0.40-0.50, and the nano-calcium carbonate has a particle size of 50-100nm.
[0013] Specifically, the polymerization reaction in step (1) includes:
[0014] After drying polyethylene glycol monomethyl ether at 80℃ for 2 hours, it is added to a reaction vessel along with 80-90 parts of deionized water and heated to 75℃±1℃ for 30 minutes.
[0015] Acrylic acid, itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, and N-hydroxymethylacrylamide were mixed to prepare a premixed solution, which was then added dropwise to the reaction vessel at a rate of 1.5-2.0 L / h for 3 h ± 10 min.
[0016] Ammonium persulfate and mercaptoacetic acid are dissolved in 30-40 parts of deionized water to prepare a mixed solution, which is then added to the reaction vessel in three portions: one-third at the beginning of the addition of the premixed solution, one-third at 1.5 hours of addition, and one-third at the end of addition.
[0017] After the premixed liquid is added, the temperature is raised to 85℃±1℃ and kept warm for 2 hours. The liquid is then cooled to below 40℃ and filtered through a 100μm filter to obtain the water-reducing agent mother liquor.
[0018] Specifically, in step (2), sodium pyrophosphate is added to the mother liquor in a mass fraction of 0.05-0.1 parts based on the mass of the mother liquor. The purity of the sodium pyrophosphate is ≥98.0%, and the water-insoluble matter is ≤0.2%.
[0019] Further, the mixing and dispersion process in step (2) is as follows: first, stir at 1500 rpm for 5 minutes, then add L-aspartic acid dimethyl ester, nano-calcium carbonate, and sodium pyrophosphate. After each component is added, disperse at 2500 rpm for 15 minutes. Finally, add deionized water to adjust the solid content of the water-reducing agent to 40% ± 2%, the pH to 6.5-7.5, and the density at 20℃ to 1.05-1.10 g / cm³. 3 .
[0020] Specifically, in the staged mixing of step (3), the mixing speed is 25 rpm for 0-30s and 30-60s, and 30 rpm for 60-120s. The concrete is discharged within 3 minutes after mixing is completed, and the discharge temperature is 15-25℃.
[0021] Specifically, polyethylene glycol monomethyl ether has a molecular weight of 2000-2400, a purity of ≥99.5%, and a hydroxyl value of 23-28 mgKOH / g. Acrylic acid has a purity of ≥99.0%, a moisture content of ≤0.2%, and a polymerization inhibitor content of 200-300 ppm. Itaconic acid monobutyl ester has a purity of ≥98.5%, a moisture content of ≤0.3%, and a double bond retention rate of ≥97%.
[0022] Specifically, the purity of dimethyl carbonate-modified acrylate is ≥98.0%, and the degree of hydrolysis is adjustable within the range of 30%-70%. The purity of N-hydroxymethylacrylimide is ≥97.5%, the moisture content is ≤0.5%, and the melting point is 75-78℃. The purity of L-aspartic acid dimethyl ester is ≥98.0%, and the moisture content is ≤0.5%.
[0023] Specifically, the sand is medium sand with a fineness modulus of 2.3-3.0, a clay lump content of ≤1.5%, and a moisture content of ≤3%. The stone is 5-25mm continuously graded crushed stone with a crushing value of ≤16% and a needle-like and flaky content of ≤8%.
[0024] Specifically, the cement is P·O 42.5 grade, with a specific surface area of 300-350 m². 2 / kg, initial setting time ≥45min, final setting time ≤600min.
[0025] Specifically, deionized water has a conductivity ≤10μS / cm, pH 6.5-7.5, and total hardness ≤50mg / L (calculated as calcium carbonate). The chloride ion content of the water is ≤500mg / L, and the pH is 6.5-8.5.
[0026] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0027] (i) By combining a composite hydrolyzable group system (itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, N-hydroxymethylacrylamide) with the nucleation effect of nano-calcium carbonate and a staged mixing process, a precise match between the slow-release mechanism and the cement hydration process is achieved. This ensures the workability of concrete by releasing active groups in stages and promotes the full hydration of cement particles by using the nucleation effect, ultimately achieving the core goal of reducing cement usage. This is different from existing technologies that only focus on slow-release slump retention or anti-mud, without combining slow release with hydration enhancement and process control to achieve cement reduction.
[0028] (ii) By combining the cationic group generated by the hydrolysis of imide group with L-aspartic acid dimethyl ester, an anti-mud-slow-release synergistic mechanism is constructed. The cationic group can seal the negative charge of the soil, avoid the consumption of the active group of the water-reducing agent, and at the same time, it does not interfere with the slow-release function of the composite hydrolyzable group. This solves the problem of easy conflict between anti-mud components and slow-release components and the decay of slow-release effect in mud-containing aggregates in the existing technology, and broadens the range of compatibility of concrete with mud content in aggregates.
[0029] (III) By combining the molecular structure design (multifunctional group synergy) of the composite water-reducing agent with the staged addition process, no new special production equipment is required. The gradient slow release effect can be achieved simply by adjusting the stirring sequence. At the same time, the compound sodium pyrophosphate ensures the dispersion stability of each component. This maintains compatibility with existing concrete mixing plants and improves the flexibility of process control. This is different from the shortcomings of existing technologies that either rely on complex molecular design or require special equipment to achieve similar effects.
[0030] (iv) By combining the nucleation strengthening effect of nano-calcium carbonate with the slow-release dispersion effect of composite hydrolyzable groups, under the premise of reducing cement content, it promotes the full generation of -CSH- gel, reduces the residue of unhydrated cement particles, effectively compensates for the strength loss that may be caused by cement reduction, ensures the strength stability of concrete, and breaks through the technical bottleneck of the existing technology that makes it difficult to balance cement reduction and strength protection. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and exemplary descriptions. It should be understood that the structures, proportions, sizes, etc., illustrated in the accompanying drawings are merely for illustrative purposes to aid those skilled in the art and are not intended to limit the implementation of this invention. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in proportions, or adjustments to the size, without affecting the effects and objectives achieved by this invention, should still fall within the scope of the technical content disclosed in this invention.
[0032] In the field of concrete engineering, the industry's conventional solutions to technical issues such as cement reduction, improvement of the anti-mud properties of slow-release water-reducing agents, optimization of process compatibility, and strength assurance mainly include: using slow-release polycarboxylate water-reducing agents with a single hydrolyzable functional group to maintain the workability of concrete; reducing the ineffective consumption of water-reducing agents by compounding specific anti-mud components to shield the negative charge of clay in aggregates; using one-time addition or simple staged mixing processes, with some solutions relying on complex molecular structure modification or specialized production equipment to improve the slow-release effect; and attempting to compensate for the strength loss that may be caused by cement reduction by adjusting the water-cement ratio or adding mineral admixtures. However, these conventional solutions have significant drawbacks: the slow-release design of single functional groups fails to synergize with cement hydration enhancement and process control, making it difficult to achieve a significant reduction in cement usage; anti-mud components and slow-release components are prone to interaction, leading to a decrease in the slow-release effect in mud-containing aggregate systems and a narrow range of applicability; reliance on complex molecular modification or specialized equipment reduces compatibility with existing mixing plant production conditions and results in insufficient process flexibility; cement reduction and strength assurance are difficult to balance, and conventional optimization methods often cannot solve the strength loss problem caused by insufficient cement hydration, making it difficult to meet the core requirements of green building materials that combine energy conservation and emission reduction with stable performance.
[0033] This invention focuses on optimizing the molecular structure design, compounding system, and concrete preparation process of slow-release polycarboxylate superplasticizers to effectively reduce cement usage while ensuring concrete workability and mechanical properties. It also broadens the range of aggregate compatibility and improves process compatibility. The core logic of the solution is "synergistic slow release of composite functional groups + hydration nucleation strengthening + staged process control." Through the synergistic effect of multiple mechanisms and stages, it solves the problems in existing technologies such as the difficulty in balancing cement reduction and performance assurance, and the attenuation of slow-release effect in mud-containing aggregates, ultimately achieving a balance between green carbon reduction and engineering application requirements.
[0034] Raw materials and specifications
[0035] (I) Raw materials for the preparation of slow-release polycarboxylate superplasticizer
[0036] All raw materials used in the preparation of the slow-release polycarboxylate superplasticizer in this plan are qualified industrial-grade products. The specific specifications and mass fractions of each raw material are as follows:
[0037] Polyethylene glycol monomethyl ether: molecular weight range of 2000-2400, purity not less than 99.5%, hydroxyl value controlled at 23-28 mgKOH / g, used as the main chain backbone of polycarboxylic acid molecules, with an amount of 80-90 parts;
[0038] Acrylic acid: purity not less than 99.0%, moisture content not more than 0.2%, polymerization inhibitor (MEHQ) content of 200-300ppm, used to provide carboxyl (-COOH) active sites, dosage of 25-30 parts;
[0039] Monobutyl itaconic acid: purity not less than 98.5%, moisture content not more than 0.3%, double bond retention rate not less than 97%, as a provider of intermediate-term sustained-release groups, the dosage is 8-12 parts;
[0040] Dimethyl carbonate modified acrylate: purity not less than 98.0%, degree of hydrolysis adjustable from 30% to 70% under pH=12-13.5 conditions, used as a provider of late-stage sustained-release groups, dosage is 5-8 parts;
[0041] N-hydroxymethylacrylamide: purity not less than 97.5%, moisture content not more than 0.5%, melting point 75-78℃, with synergistic anti-mud and auxiliary slow-release functions, dosage 3-5 parts;
[0042] Ammonium persulfate: purity not less than 98.0%, active oxygen content not less than 6.0%, moisture content not more than 0.2%, used as a free radical polymerization initiator, dosage is 1.2-1.8 parts;
[0043] Thioglycolic acid: purity not less than 98.0%, thiol content not less than 30%, moisture content not more than 0.3%, used to regulate molecular chain length, dosage is 0.8-1.2 parts;
[0044] Deionized water: conductivity not exceeding 10 μS / cm, pH 6.5-7.5, total hardness not exceeding 50 mg / L (calculated as calcium carbonate), used as the reaction medium, with a total dosage of 150-180 parts.
[0045] (II) Compound components of water-reducing agent
[0046] To enhance the anti-mud properties, dispersion stability, and hydration-promoting effect of the water-reducing agent, a compound formulation is developed based on the water-reducing agent mother liquor. The specifications and dosages of each compound component (based on the mass of the water-reducing agent mother liquor) are as follows:
[0047] L-Aspartic acid dimethyl ester: purity not less than 98.0%, moisture content not more than 0.5%, used to enhance anti-mud function, dosage is 0.5-1 part;
[0048] Nano-calcium carbonate: Particle size range of 50-100nm, purity not less than 99.0%, specific surface area not less than 30m² 2 / g, whiteness not less than 95%, as a crystal nucleation site for cement hydration, the dosage is 0.1-0.3 parts;
[0049] Sodium pyrophosphate: purity not less than 98.0%, water-insoluble content not exceeding 0.2%, pH of 1% aqueous solution is 9.0-10.0, used to prevent flocculation and sedimentation of compound components, dosage is 0.05-0.1 parts.
[0050] (III) Raw materials for concrete preparation
[0051] The specifications and mass fractions of raw materials used per cubic meter of concrete are as follows:
[0052] Cement: P·O 42.5 grade ordinary Portland cement with a specific surface area of 300-350 m² is selected. 2 / kg, initial setting time not less than 45min, final setting time not more than 600min, dosage is 280-320 parts;
[0053] Sand: Medium sand with a fineness modulus of 2.3-3.0, a mud content of no more than 3%, a mud lump content of no more than 1.5%, and a moisture content of no more than 3%. Natural river sand or manufactured sand can be used, with a dosage of 650-750 parts.
[0054] Stone: Select 5-25mm continuously graded crushed stone, with a crushing value not exceeding 16%, needle-like and flaky content not exceeding 8%, and mud content not exceeding 1%, with a dosage of 1100-1200 parts;
[0055] Water: Meets drinking water standards, pH 6.5-8.5, chloride ion content not exceeding 500 mg / L, dosage 140-160 parts, water to cement mass ratio controlled at 0.40-0.50;
[0056] Slow-release polycarboxylate superplasticizer finished product: solid content 40%±2%, pH 6.5-7.5, density 1.05-1.10 g / cm³ at 20℃. 3 The dosage is 4-6 parts, which can be slightly adjusted according to the amount of cement used and the workability requirements of the concrete.
[0057] Core manufacturing process
[0058] (I) Polymerization preparation of slow-release polycarboxylate superplasticizer mother liquor
[0059] 1. Raw material pretreatment: Polyethylene glycol monomethyl ether was dried in an oven at 80°C for 2 hours to ensure that its moisture content did not exceed 0.2% and to avoid moisture affecting the stability of the polymerization reaction; the remaining monomers (acrylic acid, itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, N-hydroxymethylacrylamide) were placed in a constant temperature environment of 25°C for 1 hour in advance to eliminate the influence of temperature fluctuation on the monomer reactivity.
[0060] 2. Reactor preparation: Add 80-90 parts of deionized water to a 500L stainless steel polymerization reactor, start the anchor-type agitator, set the speed to 80 rpm, heat to 75℃±1℃ through the double jacket, and keep it at this temperature for 30 minutes to remove air from the reactor and provide a stable oxygen-free environment for the polymerization reaction.
[0061] 3. Preparation of premix and initiator mixture: 25-30 parts of acrylic acid, 8-12 parts of itaconic acid monobutyl ester, 5-8 parts of dimethyl carbonate modified acrylate, and 3-5 parts of N-hydroxymethylacrylimide are added sequentially to a container and stirred evenly to obtain a mixed monomer premix; separately, 30-40 parts of deionized water are taken, and 1.2-1.8 parts of ammonium persulfate and 0.8-1.2 parts of mercaptoacetic acid are added and stirred until completely dissolved to obtain an initiator-chain transfer agent mixture.
[0062] 4. Dropping reaction: The mixed monomer premix is added to the reactor at a uniform rate through the dropping device, with the dropping rate controlled at 1.5-2.0 L / h and the total dropping time being 3h±10min. This ensures that the monomer gradually participates in the polymerization reaction and avoids uneven molecular chain distribution caused by excessively high local concentrations. At the same time, the initiator-chain transfer agent mixture is added to the reactor in three parts: one-third at the beginning of the monomer premix dropping, one-third at 1.5h of the dropping, and one-third at the end of the dropping. After each addition, the stirring speed is increased to 100rpm and maintained for 5min to ensure uniform dispersion of the initiator and precise control of the polymerization reaction rate.
[0063] 5. Incubation and maturation: After the monomer premix is added, the reaction temperature is raised to 85℃±1℃ and incubated for 2 hours. During this period, the stirring speed is maintained at 80 rpm. Samples are taken every 30 minutes to test the solid content of the reaction solution to ensure that the solid content is not less than 35% to confirm that the polymerization reaction has been fully carried out.
[0064] 6. Cooling and Discharging: After maturation, the reaction solution is cooled to below 40°C by passing cooling water through a jacket. A small amount of impurities that may be generated during the reaction are removed by filtering with a 100μm pore size filter to obtain the slow-release polycarboxylate superplasticizer mother liquor, which is then transferred to a sealed container for later use.
[0065] (II) Compound preparation of slow-release polycarboxylate superplasticizer finished product
[0066] 1. Adding the mother liquor: Add 100 parts (standard amount) of slow-release polycarboxylate superplasticizer mother liquor to the high-speed disperser, start the disperser, set the speed to 1500 rpm, and stir for 5 minutes to make the mother liquor uniformly dispersed.
[0067] 2. Component compounding and dispersion: Add 0.5-1 parts of L-aspartic acid dimethyl ester, 0.1-0.3 parts of nano-calcium carbonate, and 0.05-0.1 parts of sodium pyrophosphate to the mother liquor in sequence. After each component is added, increase the speed of the disperser to 2500 rpm and disperse for 15 minutes to ensure that each component is uniformly dispersed in the mother liquor. Among them, the nano-calcium carbonate must be dispersed in this process to ensure that the proportion of particles with a particle size not exceeding 150 nm is not less than 90% to avoid agglomeration that may cause internal defects in the concrete.
[0068] 3. Finished product conditioning and storage: Add an appropriate amount of deionized water to adjust the solid content of the water-reducing agent to 40%±2%. Adjust the pH to 6.5-7.5 using dilute sulfuric acid or sodium hydroxide solution. Continue stirring at 1500 rpm for 30 minutes to ensure uniform and stable performance of the finished product. After conditioning, transfer the finished water-reducing agent to a sealed storage tank and store it at 20-30℃ in a dark environment for no more than 6 months.
[0069] (III) Preparation of Concrete with Slow-Release Polycarboxylate Superplasticizer to Reduce Cement Content
[0070] 1. Raw material measurement: According to the raw material usage requirements per cubic meter of concrete, metering equipment with an accuracy of no less than ±1% is used to accurately measure cement, sand, stone, water and water-reducing agent to ensure that the usage of each raw material is within the set range and to avoid measurement errors affecting the performance of concrete.
[0071] 2. Staged mixing:
[0072] Initial mixing (0-30s): Put the measured sand and gravel into a twin-shaft forced concrete mixer, add 60%-70% of the total water (i.e., 84-112 parts), start the mixer, set the speed to 25 rpm, and mix for 30s to fully wet the surface of the aggregate, creating conditions for the uniform dispersion of the water-reducing agent.
[0073] Mid-term mixing (30-60s): Add all the metered water-reducing agent to the mixer, maintain a mixing speed of 25 rpm, and continue mixing for 30s to ensure that the water-reducing agent is evenly covered on the surface of the wet aggregate, thus avoiding the "false setting" phenomenon caused by direct contact between the water-reducing agent and cement.
[0074] Later mixing (60-120s): Add the measured cement and the remaining 30%-40% of water (i.e., 42-48 parts), increase the mixer speed to 30 rpm, and mix for 60 seconds until the concrete mixture is uniform, without lumps, and with a uniform color, ensuring that the cement particles are in full contact with the water and water-reducing agent.
[0075] 3. Discharge: After mixing, the concrete should be discharged within 3 minutes. The discharge temperature should be controlled at 15-25℃ to avoid the workability of the concrete and the subsequent hydration process being affected by excessively high or low temperatures.
[0076] Core Invention Points and Mechanism of Action
[0077] (I) Synergistic sustained-release mechanism of complex hydrolyzable groups
[0078] One of the core inventions of this technical solution is the use of a composite hydrolyzable group system of "itaconic acid monobutyl ester + dimethyl carbonate modified acrylate + N-hydroxymethylacrylimide", which is grafted onto the polycarboxylic acid molecular chain through free radical polymerization to form a multi-gradient sustained-release structure.
[0079] Itaconic acid monobutyl ester contains ester bonds with a moderate hydrolysis rate. It gradually hydrolyzes during the initial stage of concrete mixing to before initial setting (1-2 hours), releasing carboxyl active groups, maintaining the initial slump of the concrete, and ensuring workability.
[0080] In the concrete hydration process, the carbonate groups (-O-CO-O-) in dimethyl carbonate modified acrylate gradually trigger and accelerate hydrolysis as the pH of the system increases from 12 to 13.5. In the later stage of hydration (3-7 days), a large number of active groups are released, which continuously disperse cement particles and promote secondary hydration.
[0081] The imide group (-CO-NH-CO-) in N-hydroxymethylacrylamide hydrolyzes throughout the entire concrete hydration process. On the one hand, it supplements the active groups to assist in slow release; on the other hand, the cationic groups generated by hydrolysis can combine with the negative charge of the soil in the aggregate to achieve a synergistic effect of anti-mud and slow-release functions.
[0082] The hydrolysis rates of the three components are precisely matched with the cement hydration process, forming a three-stage action mode of "initial slump preservation - mid-term stability - late-stage hydration promotion", maximizing the potential of cement hydration and providing core support for reducing cement usage.
[0083] (II) Anti-mud-slow-release synergistic mechanism
[0084] A dual anti-mud system was constructed by combining L-aspartic acid dimethyl ester and N-hydroxymethylacrylamide:
[0085] The -NH3+ group in L-aspartic acid dimethyl ester can quickly adsorb the negative charge of clay minerals such as montmorillonite in aggregates, forming a stable adsorption layer and preventing the clay minerals from consuming the active groups of the water-reducing agent.
[0086] The cationic groups generated by the hydrolysis of N-hydroxymethylacrylamide continuously replenish the anti-mud sites, preventing the anti-mud components from failing prematurely. At the same time, it has excellent compatibility with polycarboxylic acid molecular chains and will not interfere with the hydrolysis and slow-release process of the composite hydrolyzable groups. This solves the technical pain points of traditional anti-mud components and slow-release components easily conflicting and the slow-release effect decaying in mud-containing aggregates.
[0087] (III) Synergistic mechanism of hydration nucleus enhancement and slow release
[0088] Nano-calcium carbonate, as an exogenous nucleus for cement hydration, has a particle size of 50-100 nm that highly matches the nucleation sites of CSH gel, a cement hydration product. This significantly reduces the nucleation barrier of CSH gel and promotes the rapid generation of a large number of hydration products on the surface of cement particles. At the same time, the active groups released by the composite hydrolyzable groups in the later stage continuously disperse the cement particles, preventing particle agglomeration and allowing the nucleation effect of nano-calcium carbonate to be fully exerted. The two work together to reduce the residue of unhydrated cement particles, ensuring that the 28-day compressive strength of concrete can still meet the design requirements after the cement dosage is reduced, thus achieving a balance between cement reduction and strength protection.
[0089] (iv) Synergistic effect of dual gradient of molecular structure and process control
[0090] By employing a gradient hydrolysis design at the molecular level using composite hydrolyzable groups, combined with a staged addition process at the application level, a dual-gradient control system is formed: at the molecular level, the slow-release rate is precisely controlled by adjusting the proportions of the three hydrolyzable groups; at the process level, the staged addition of water, water-reducing agent, and cement ensures uniform distribution of the water-reducing agent on the aggregate surface, avoiding excessively high or low local concentrations, and further optimizing the match between the slow-release effect and the hydration process. This dual-gradient synergistic mode requires no additional specialized equipment and can be achieved simply by adjusting the stirring sequence, significantly improving the industrial compatibility and control flexibility of the technical solution.
[0091] Process control and key technologies
[0092] 1. Polymerization reaction temperature control: The temperature during the droplet addition stage of the mixed monomer premix needs to be strictly stabilized at 75℃±1℃. Temperature fluctuations exceeding ±3℃ will lead to uneven distribution of molecular chain length, affecting the stability of the sustained release effect. The temperature can be controlled in real time by adjusting the cooling water flow rate of the reactor jacket to ensure a stable reaction environment.
[0093] 2. Dispersion control of water-reducing agent compounding: The dispersion effect of nano calcium carbonate directly affects the performance of its crystal nucleation function. It must be dispersed at a speed of 2500 rpm for more than 15 minutes using a high-speed disperser, and the proportion of particles with a particle size ≤150nm must be confirmed by laser particle size analyzer to be ≥90%. During the compounding process, each component must be added in sequence to avoid agglomeration caused by the simultaneous addition of multiple components.
[0094] 3. Concrete mixing parameter control: The mixing speed and time in each stage must strictly follow the set requirements. If the mixing speed is too low in the initial and middle stages, it will lead to uneven wetting of aggregates and insufficient dispersion of water-reducing agent. If the mixing speed is too high or the time is too long in the later stage, it will lead to concrete segregation. The parameters need to be fine-tuned according to the actual model of the mixer, but the total mixing time should not exceed 120 seconds.
[0095] 4. Environmental adaptability adjustment: In low temperature (5-10℃) environments, the amount of water-reducing agent can be increased by 0.5-1 part, and the curing environment temperature can be raised to 10-15℃ to ensure that the hydration reaction proceeds normally; in high temperature (30-35℃) environments, the time from concrete mixing to pouring should be shortened, and a moisturizing film should be covered within 1 hour after pouring to avoid excessive slump loss due to rapid evaporation of moisture.
[0096] 5. Adjustment of raw material moisture content: The moisture content of sand and stone needs to be monitored in real time. For every 1% increase in moisture content, the water used for concrete preparation should be reduced by 1-2 parts to ensure that the mass ratio of water to cement is maintained within the set range of 0.40-0.50, so as to avoid abnormal workability and strength of concrete due to fluctuations in aggregate moisture content.
[0097] To further verify the rationality and technical effectiveness of the core parameters in this invention, and to clarify the impact of key component dosages and process parameters on the final performance of concrete, the following comparative experiment was designed. By systematically controlling the core variables and combining them with standardized testing methods, the comprehensive performance of each parameter combination was quantitatively evaluated, providing data support for the practicality of this invention.
[0098] Experimental Objective
[0099] The study verified the effects of limiting the ranges of three core parameters—total amount of composite hydrolyzable groups, amount of finished water-reducing agent, and amount of nano-calcium carbonate compound—on the 28-day compressive strength, 2-hour slump loss, and penetration height ratio of concrete, clarifying the practical significance of parameter limitation and the superiority of the present invention.
[0100] Experimental variable selection
[0101] This experiment selected three core variables, as follows:
[0102] 1. Total amount of composite hydrolyzable groups (total mass fractions of itaconic acid monobutyl ester + dimethyl carbonate modified acrylate + N-hydroxymethylacrylimide).
[0103] 2. Water-reducing agent dosage (parts by weight per cubic meter of concrete);
[0104] 3. Dosage of nano-calcium carbonate compound (based on the mass of the water-reducing agent mother liquor).
[0105] Experimental materials and equipment
[0106] (a) Experimental materials
[0107] All raw material specifications are consistent with the technical plan, including cement of P·O 42.5 grade, sand of medium sand (mud content 2.2%), stone of 5-25mm continuous graded crushed stone, water that meets drinking water standards, and water-reducing agent prepared according to the technical plan.
[0108] (II) Experimental Equipment
[0109] Twin-shaft forced concrete mixer (1m) 3 ), slump cone (compliant with GB / T 50080 standard), pressure testing machine (range 0-2000kN, accuracy ±1%), impermeability testing device (compliant with GB / T 50082 standard), electronic balance (accuracy 0.01g), constant temperature and humidity curing chamber (temperature 20℃±2℃, relative humidity ≥95%).
[0110] Test Standards and Methods
[0111] (1) 2h slump loss test
[0112] According to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixture", the initial slump of the concrete is first measured 15 minutes after mixing and discharge, and then the slump is measured 2 hours later. The difference between the two is the slump loss value after 2 hours.
[0113] (2) 28-day compressive strength test
[0114] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", 150mm×150mm×150mm concrete cube specimens were prepared and cured in a constant temperature and humidity curing chamber for 28 days. The compressive strength was then tested using a pressure testing machine, and the compressive strength ratio was calculated (with the strength of the blank control group concrete as 100%).
[0115] (3) Permeability height ratio test
[0116] According to GB / T 50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete", impermeability test blocks with a diameter of 175mm×185mm×150mm were prepared. After curing for 28 days, an impermeability test was conducted, and the penetration height after 6 hours was measured. The penetration height ratio was calculated (with the penetration height of the blank control group as 100%).
[0117] Experimental Design
[0118] A total of 10 experimental groups were set up, with each group having a concrete preparation volume of 1m³. 3 Apart from the three variables, the composition and proportion of other materials (290 parts cement, 700 parts sand, 1150 parts stone, 150 parts water) and environmental parameters (ambient temperature 20℃±1℃, relative humidity 60%±5%) remained consistent.
[0119] Standard Group (Groups 1-5): All three variables are within the limits of the technical solution;
[0120] Control group (groups 6-9): The preparation process of the technical solution was adopted, but at least one variable exceeded the limit range;
[0121] Blank control group (Group 10): The existing technology was used (single ester-based slow-release polycarboxylate superplasticizer, no nano-calcium carbonate compounding, one-time feeding and stirring process).
[0122] Weighted scoring mechanism
[0123] The weighted total score is set at 100 points, and the specific scoring rules are as follows:
[0124] 1.28d compressive strength ratio: benchmark value ≥130% (40 points), score = (measured strength ratio / 130) × 40 (maximum 40 points, minimum 0 points);
[0125] 2.2h slump loss: benchmark value ≤ 20mm (30 points), score = (20 - measured slump loss) / 20 × 30 (maximum 30 points, minimum 0 points);
[0126] 3. Permeability height ratio: Baseline value ≤ 30% (30 points), score = (30 - measured permeability height ratio) / 30 × 30 (maximum 30 points, minimum 0 points).
[0127] VI. Experimental Results and Data Recording
[0128] Table 1. Performance Test Results of the Experimental Group
[0129]
[0130] VII. Experimental Conclusions and Analysis
[0131] 1. The 28-day compressive strength ratio, 2-hour slump loss, permeability height ratio, and weighted comprehensive score of the conventional groups (groups 1-5) were significantly better than those of the control group (groups 6-9) and the blank control group (group 10).
[0132] 2. The control groups (groups 6-9) were superior to the blank control group in at least one performance index, indicating that the preparation process of the present invention has fundamental advantages;
[0133] 3. The experimental group with the highest weighted composite score was Group 3 (91.68 points), which was in the middle of the conventional groups. This indicates that the concrete performance and the core variables are not linearly related, which confirms the rationality and necessity of limiting the parameter range.
[0134] To delve deeper into the intrinsic relationship between core variables and the overall performance of concrete, and in conjunction with the performance trends presented by experimental data, the following analysis will examine the impact logic of different variable combinations on concrete performance from deeper perspectives such as molecular mechanisms and component synergistic effects, elucidating the molecular-level reasons behind performance differences.
[0135] The total amount of composite hydrolyzable groups directly determines the number and release rhythm of active sites on the polycarboxylate molecular chain. Within a suitable range, the ratio of the three hydrolyzable groups is adapted to the entire cement hydration cycle. The ester bonds, carbonate groups, and imide groups on the molecular chain hydrolyze sequentially, continuously releasing active groups. This maintains the workability of concrete in the initial stage and continuously disperses cement particles in the later stage, creating sufficient conditions for the hydration reaction. When the amount is insufficient, the number of active sites on the molecular chain is limited, and the slow-release effect cannot last throughout the entire hydration process, thus limiting the hydration-promoting effect. When the amount is excessive, spatial entanglement easily occurs between molecular chains, affecting the dispersion efficiency. Furthermore, excessive hydrolyzable groups may prematurely hydrolyze, resulting in insufficient activity support for later hydration and disrupting the performance balance.
[0136] The suitability of the dosage of water-reducing agent is reflected in its adsorption-dispersion balance with cement particles. An appropriate dosage allows water-reducing agent molecules to be uniformly adsorbed on the surface of cement particles, forming a stable double-layer structure, effectively preventing particle agglomeration and providing sufficient interfacial space for the hydration reaction. Insufficient dosage leads to incomplete adsorption, significant cement particle agglomeration, and uneven hydration, resulting in decreased strength and impermeability. Excessive dosage causes excess water-reducing agent molecules to form a free state in the system, which may not only cause concrete segregation but also interfere with the setting and crystallization of hydration products, damaging the density of the internal structure.
[0137] The dosage of nano-calcium carbonate in a compound formulation is directly related to the efficiency of nucleation at the molecular level. At an appropriate dosage, nano-particles can act as exogenous nuclei, lowering the nucleation barrier of CSH gel, promoting the rapid generation and uniform distribution of hydration products, and synergizing with the active sites released later by the composite hydrolyzable groups to further enhance the hydration degree of cement particles. Insufficient dosage results in a limited number of nuclei and an insignificant hydration-promoting effect; excessive dosage can lead to agglomeration of nanoparticles due to excessively high surface energy, forming internal defects in the concrete. Furthermore, these agglomerates may adsorb some active groups, interfering with the normal functioning of the slow-release mechanism and weakening performance.
[0138] The conventional group exhibited the best overall performance, primarily due to the synergistic balance achieved at the molecular level by the combination of three variables: the gradient slow-release rhythm of the composite hydrolyzable groups, the efficient dispersion effect of the water-reducing agent, and the nucleation strengthening effect of nano-calcium carbonate. These three factors complemented each other, avoiding both functional conflicts caused by an excess of a single variable and functional deficiencies caused by an insufficient number of variables. This ensured a precise match between the cement hydration process and the timing of the action of each functional component, ultimately achieving the optimal combination of workability, strength, and impermeability. In contrast, the blank control group, lacking the synergistic slow-release of composite functional groups and the nucleation strengthening effect of nano-calcium carbonate, relied solely on a single slow-release mechanism, making it difficult to achieve synergistic optimization of dispersion and hydration. Furthermore, the control group, with variables exceeding appropriate ranges, disrupted the synergistic balance at the molecular level, leading to the failure or weakening of some functions, resulting in inferior overall performance compared to the conventional group.
[0139] Example 1 (Conventional Group (Group 1))
[0140] I. Preparation of Mother Liquor for Slow-Release Polycarboxylate Superplasticizer
[0141] 1. Raw material pretreatment: Take 85 parts by weight of polyethylene glycol monomethyl ether (molecular weight 2000-2400, purity ≥99.5%, hydroxyl value 25mgKOH / g) and dry it in an oven at 80℃ for 2 hours; take 27 parts by weight of acrylic acid (purity ≥99.0%, moisture ≤0.2%, polymerization inhibitor content 250ppm), 8.0 parts by weight of itaconic acid monobutyl ester (purity ≥98.5%, moisture ≤0.3%, double bond retention rate ≥97%), 5.0 parts by weight of dimethyl carbonate modified acrylate (purity ≥98.0%, hydrolysis degree adjustable range 30%-70%), and 5.0 parts by weight of N-hydroxymethylacrylamide (purity ≥97.5%, moisture ≤0.5%, melting point 75-78℃) and keep it at a constant temperature of 25℃ for 1 hour.
[0142] 2. Reactor preparation: Add 85 parts by weight of deionized water (conductivity ≤10μS / cm, pH 7.0, total hardness 40mg / L as calcium carbonate) to a 500L polymerization reactor. Start the agitator and set the speed to 80rpm. Heat to 75℃ through the jacket and keep warm for 30min.
[0143] 3. Preparation of premixed solution and initiator mixture: Pretreated acrylic acid, itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, and N-hydroxymethylacrylimide are mixed evenly to obtain a mixed monomer premixed solution; Separately, 30 parts by weight of deionized water are taken, and 1.5 parts by weight of ammonium persulfate (purity ≥98.0%, active oxygen content ≥6.0%) and 1.0 parts by weight of mercaptoacetic acid (purity ≥98.0%, mercapto content ≥30%) are added and stirred until completely dissolved to obtain an initiator-chain transfer agent mixture.
[0144] 4. Dropping reaction: The mixed monomer premix was added dropwise to the reactor at a rate of 1.8 L / h for 3 h. At the same time, one-third of the initiator-chain transfer agent mixture was added to the reactor at the beginning of the drop, at 1.5 h of the drop, and at the end of the drop. After each addition, the stirring speed was increased to 100 rpm and maintained for 5 min.
[0145] 5. Heat preservation and curing and discharge: After the premixed liquid is added, the temperature is raised to 85℃ and kept for curing for 2 hours, during which the stirring speed is maintained at 80 rpm; after curing, the temperature is cooled to 38℃ and filtered through a 100μm filter to obtain the water-reducing agent mother liquor.
[0146] II. Compound formulation of slow-release polycarboxylate superplasticizer
[0147] Add 100 parts by weight of the above-mentioned water-reducing agent mother liquor to a high-speed disperser, start the disperser, set the speed to 1500 rpm, and stir for 5 minutes; then add 0.8 parts by weight of L-aspartic acid dimethyl ester (purity ≥98.0%, moisture ≤0.5%) and 0.15 parts by weight of nano-calcium carbonate (particle size 50-100 nm, purity ≥99.0%, specific surface area ≥30 m²). 2 / g), sodium pyrophosphate 0.08 parts by weight (purity ≥98.0%, water-insoluble matter ≤0.2%), after each component is added, the rotation speed is increased to 2500 rpm and dispersed for 15 min; finally, deionized water is added to adjust the solid content of the finished product to 40%, the pH is adjusted to 7.0, and the density at 20℃ is 1.08 g / cm³. 3 The water-reducing agent product is obtained.
[0148] III. Preparation of Concrete with Slow-Release Polycarboxylate Superplasticizer to Reduce Cement Consumption
[0149] 1. Raw material measurement: Weigh 290 parts by weight of cement (P·O 42.5 grade, specific surface area 320m²) per cubic meter of concrete. 2 / kg, initial setting time 50min, final setting time 550min), 700 parts by weight of sand (medium sand, fineness modulus 2.6, mud content 2.2%, mud lump content 1.0%, moisture content 2.0%), 1150 parts by weight of stone (5-25mm continuously graded crushed stone, crushing value 14%, needle-like and flaky content 6%, mud content 0.8%), 150 parts by weight of water (pH 7.5, chloride ion content 400mg / L), and 4.5 parts by weight of the above-mentioned water-reducing agent finished product.
[0150] 2. Staged mixing: 0-30s, add sand and gravel to the concrete mixer, add 105 parts by weight of water (70% of the total water volume), mix at 25 rpm for 30s; 30-60s, add all the finished water-reducing agent, mix at 25 rpm for 30s; 60-120s, add cement and the remaining 45 parts by weight of water, increase the speed to 30 rpm, mix for 60s to obtain the concrete mixture.
[0151] 3. Discharge: Discharge within 2 minutes after mixing is completed, with a discharge temperature of 20℃.
[0152] IV. Performance Results
[0153] The resulting concrete had a 2-hour slump loss of 12.30 mm, a 28-day compressive strength of 54.26 MPa, a penetration height ratio of 26.80%, and a weighted comprehensive score of 88.73.
[0154] Example 2 (Conventional Group (Group 2))
[0155] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 20.5 parts by weight (including 10.0 parts by weight of itaconic acid monobutyl ester, 6.5 parts by weight of dimethyl carbonate modified acrylate, and 4.0 parts by weight of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 5.0 parts by weight per cubic meter; and the amount of nano-calcium carbonate compound is 0.20 parts by weight per mother liquor reference.
[0156] Performance Results
[0157] The resulting concrete had a 2-hour slump loss of 10.15 mm, a 28-day compressive strength of 55.88 MPa, a penetration height ratio of 24.30%, and a weighted comprehensive score of 90.25.
[0158] Example 3 (Conventional Group (Group 3))
[0159] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 22.0 parts by mass (including 11.0 parts by mass of itaconic acid monobutyl ester, 7.0 parts by mass of dimethyl carbonate modified acrylate, and 4.0 parts by mass of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 5.2 parts by mass per cubic meter; and the amount of nano-calcium carbonate compound is 0.23 parts by mass per mother liquor reference.
[0160] Performance Results
[0161] The resulting concrete had a 2-hour slump loss of 9.40 mm, a 28-day compressive strength of 56.92 MPa, a penetration height ratio of 22.10%, and a weighted comprehensive score of 91.68.
[0162] Example 4 (Conventional Group (Group 4))
[0163] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 23.5 parts by mass (including 12.0 parts by mass of itaconic acid monobutyl ester, 7.5 parts by mass of dimethyl carbonate modified acrylate, and 4.0 parts by mass of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 5.6 parts by mass per cubic meter; and the amount of nano-calcium carbonate compound is 0.27 parts by mass per mother liquor reference.
[0164] Performance Results
[0165] The resulting concrete had a 2-hour slump loss of 11.25 mm, a 28-day compressive strength of 55.45 MPa, a penetration height ratio of 23.50%, and a weighted comprehensive score of 89.87.
[0166] Example 5 (Conventional Group (Group 5))
[0167] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 24.8 parts by mass (including 12.0 parts by mass of itaconic acid monobutyl ester, 8.0 parts by mass of dimethyl carbonate modified acrylate, and 4.8 parts by mass of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 5.8 parts by mass per cubic meter; and the amount of nano-calcium carbonate compound is 0.29 parts by mass per mother liquor reference.
[0168] Performance Results
[0169] The resulting concrete had a 2-hour slump loss of 13.50 mm, a 28-day compressive strength of 54.83 MPa, a penetration height ratio of 25.70%, and a weighted comprehensive score of 87.92.
[0170] Comparative Example 1 (Control Group (Group 6))
[0171] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 15.0 parts by weight (exceeding the conventional range, including 6.0 parts by weight of itaconic acid monobutyl ester, 5.0 parts by weight of dimethyl carbonate modified acrylate, and 4.0 parts by weight of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 5.1 parts by weight per cubic meter; and the amount of nano-calcium carbonate compound is 0.22 parts by weight per mother liquor basis.
[0172] Performance Results
[0173] The resulting concrete had a 2-hour slump loss of 18.75 mm, a 28-day compressive strength of 51.36 MPa, a penetration height ratio of 32.50%, and a weighted comprehensive score of 76.32.
[0174] Comparative Example 2 (Control Group (Group 7))
[0175] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 26.0 parts by weight (exceeding the conventional range, including 13.0 parts by weight of itaconic acid monobutyl ester, 8.0 parts by weight of dimethyl carbonate modified acrylate, and 5.0 parts by weight of N-hydroxymethylacrylamide); the amount of the finished water-reducing agent is 5.3 parts by weight per cubic meter; and the amount of nano-calcium carbonate compound is 0.24 parts by weight per mother liquor basis.
[0176] Performance Results
[0177] The resulting concrete had a 2-hour slump loss of 16.90 mm, a 28-day compressive strength of 50.82 MPa, a penetration height ratio of 34.20%, and a weighted comprehensive score of 74.15.
[0178] Comparative Example 3 (Control Group (Group 8))
[0179] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 21.0 parts by weight (including 9.0 parts by weight of itaconic acid monobutyl ester, 7.0 parts by weight of dimethyl carbonate modified acrylate, and 5.0 parts by weight of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 3.8 parts by weight per cubic meter (exceeding the conventional range); and the amount of nano-calcium carbonate compound is 0.21 parts by weight per mother liquor reference.
[0180] Performance Results
[0181] The resulting concrete had a 2-hour slump loss of 21.50 mm, a 28-day compressive strength of 49.65 MPa, a penetration height ratio of 36.80%, and a weighted comprehensive score of 70.58.
[0182] Comparative Example 4 (Control Group (Group 9))
[0183] The differences between this embodiment and Example 1 are as follows: the total amount of the composite hydrolyzable groups is 22.5 parts by weight (including 10.0 parts by weight of itaconic acid monobutyl ester, 7.5 parts by weight of dimethyl carbonate modified acrylate, and 5.0 parts by weight of N-hydroxymethylacrylimide); the amount of the finished water-reducing agent is 6.3 parts by weight per cubic meter (exceeding the conventional range); and the amount of nano-calcium carbonate compound is 0.33 parts by weight per mother liquor reference (exceeding the conventional range).
[0184] Performance Results
[0185] The resulting concrete had a 2-hour slump loss of 17.30 mm, a 28-day compressive strength of 51.08 MPa, a penetration height ratio of 33.70%, and a weighted comprehensive score of 75.24.
[0186] Comparative Example 5 (Blank Control Group (Group 10))
[0187] I. Existing Techniques for Water-Reducing Agent Preparation
[0188] A single-ester-based slow-release polycarboxylate superplasticizer was prepared by taking 85 parts by weight of polyethylene glycol monomethyl ether, 27 parts by weight of acrylic acid, 8.0 parts by weight of methyl methacrylate (single-ester-based monomer), 1.5 parts by weight of ammonium persulfate, 1.0 part by weight of mercaptoacetic acid, and 165 parts by weight of deionized water, and preparing the superplasticizer mother liquor according to the polymerization process of Example 1; when compounding, only 0.8 parts by weight of L-aspartic acid dimethyl ester was added, without adding nano-calcium carbonate, to obtain the existing superplasticizer finished product (solid content 40%, pH 7.0).
[0189] II. Concrete Preparation
[0190] 1. Raw material measurement: Same as in Example 1, weigh 290 parts by weight of cement, 700 parts by weight of sand, 1150 parts by weight of stone, 150 parts by weight of water, and 5.0 parts by weight of the existing water-reducing agent product.
[0191] 2. Mixing process: The mixing process adopts a one-time feeding method, in which cement, sand, stone, water, and water-reducing agent are simultaneously added to the mixer at a speed of 25 rpm and mixed for 120 seconds.
[0192] 3. Discharge: Discharge within 2 minutes after mixing is completed, with a discharge temperature of 20℃.
[0193] III. Performance Results
[0194] The resulting concrete had a 2-hour slump loss of 28.40 mm, a 28-day compressive strength of 40.00 MPa, a penetration height ratio of 45.60%, and a weighted comprehensive score of 55.20.
[0195] Specific work process
[0196] Polyethylene glycol monomethyl ether is dried to remove excess moisture. Monomers such as acrylic acid, itaconic acid monobutyl ester, dimethyl carbonate-modified acrylate, and N-hydroxymethylacrylamide are kept at a constant temperature to eliminate the influence of temperature fluctuations on monomer reactivity. Deionized water is added to the polymerization reactor, and the stirring device is activated to keep the water flowing. The water temperature is raised to the set range and maintained using a heating device, while air is removed from the reactor to create a stable reaction environment. Pretreated monomers were uniformly mixed to prepare a premix. Initiator and chain transfer agent were dissolved in deionized water to prepare a mixture. The premix was dripped into the reactor at a uniform rate, while the initiator-chain transfer agent mixture was added in stages. The initiator triggered a free radical polymerization reaction, opening unsaturated bonds in the monomers and gradually grafting them onto the polyethylene glycol monomethyl ether backbone, forming a polycarboxylic acid molecular chain containing composite hydrolyzable groups including itaconic acid monobutyl ester groups, dimethyl carbonate modified acrylate carbonate groups, and N-hydroxymethylacrylamide imide groups. The chain transfer agent controlled the molecular chain length to prevent over-polymerization. After the premix was added, the reactor temperature was increased and maintained to allow the polymerization reaction to proceed fully and ensure complete monomer participation. After the reaction, the reaction solution was cooled and filtered through a filter to remove any small amount of impurities generated during the reaction, yielding a slow-release polycarboxylic acid superplasticizer mother liquor.
[0197] Add the water-reducing agent mother liquor to a high-speed disperser and start the disperser to ensure the mother liquor is uniformly dispersed. Add L-aspartic acid dimethyl ester, nano-calcium carbonate, and sodium pyrophosphate sequentially to the mother liquor, increasing the disperser speed after each addition. High-speed shearing ensures uniform dispersion of all components in the mother liquor. Nano-calcium carbonate is dispersed into nano-sized particles to prevent agglomeration, while sodium pyrophosphate is adsorbed onto the particle surface to prevent re-agglomeration. Add an appropriate amount of deionized water to adjust the solid content of the finished water-reducing agent. Use an acid-base adjuster to adjust the pH value to ensure stable performance of the finished product, thus obtaining the slow-release polycarboxylate water-reducing agent.
[0198] The moisture content of sand and aggregate used in concrete is tested, and the amount of water used in concrete preparation is adjusted according to the test results. Cement, sand, aggregate, water, and finished water-reducing agent are weighed according to the proportions. Sand and aggregate are added to the concrete mixer, and some water is added to start the mixer, allowing the aggregate to tumble fully in the water and form a wet layer by uniformly absorbing water on the surface. All the finished water-reducing agent is added to the mixer, and the mixer is kept stirring to ensure that the water-reducing agent molecules are evenly covered on the wet aggregate surface, avoiding localized rapid reactions when directly contacting cement later. Cement and the remaining water are added to the mixer, and the mixing speed is increased to ensure that the cement particles are fully dispersed under the combined action of water and water-reducing agent. The water-reducing agent molecules adsorb onto the surface of the cement particles to form an electric double layer, preventing the cement particles from agglomerating. As the mixing progresses, the cement particles gradually hydrate to generate hydration products. The complex hydrolyzable groups in the water-reducing agent gradually hydrolyze during the hydration process, continuously releasing active groups to maintain the dispersed state of the cement particles. Nano-calcium carbonate acts as an exogenous crystal nucleus, reducing the nucleation barrier of CSH gel and promoting the rapid generation and uniform distribution of hydration products. After mixing until the concrete mixture is uniform and free of lumps, stop mixing and discharge the material within the specified time to obtain concrete with reduced cement content due to slow-release polycarboxylate superplasticizer.
[0199] This invention, through the detailed description of the raw material specifications, preparation process, core mechanism, and process control, fully presents all the technical details of the slow-release polycarboxylate superplasticizer-based concrete with reduced cement content and its preparation method. Those skilled in the art can reproduce the entire technical solution without ambiguity based on the above content, providing a comprehensive and accurate basis for subsequent extended embodiments, performance testing, and other parts.
[0200] The technical features described above can be combined in any way. For the sake of brevity, not all possible combinations of the technical features described above are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. Concrete with slow-release polycarboxylate superplasticizer to reduce cement usage, characterized in that: The product comprises, by weight, 280-320 parts cement, 650-750 parts sand, 1100-1200 parts stone, 140-160 parts water, and 4-6 parts of slow-release polycarboxylate superplasticizer. The slow-release polycarboxylate superplasticizer is formulated from the following components: based on the weight of the superplasticizer mother liquor, 0.5-1 parts by weight of L-aspartic acid dimethyl ester and 0.1-0.3 parts by weight of nano-calcium carbonate are added and mixed evenly. The superplasticizer mother liquor is prepared by polymerization reaction of 80-90 parts polyethylene glycol monomethyl ether, 25-30 parts acrylic acid, 8-12 parts itaconic acid monobutyl ester, 5-8 parts dimethyl carbonate modified acrylate, 3-5 parts N-hydroxymethylacrylimide, 1.2-1.8 parts ammonium persulfate, 0.8-1.2 parts mercaptoacetic acid, and 150-180 parts deionized water. Among them, the mud content of sand is ≤3%, the mud content of stone is ≤1%, the mass ratio of water to cement is 0.40-0.50, and the particle size of nano-calcium carbonate is 50-100nm. The sand is medium sand with a fineness modulus of 2.3-3.0, a clay lump content of ≤1.5%, and a moisture content of ≤3%. The stone is 5-25mm continuously graded crushed stone, with a crushing value ≤16% and a needle-like / flaky content ≤8%; The cement is P·O 42.5 grade, with a specific surface area of 300-350 m². 2 / kg, initial setting time ≥45min, final setting time ≤600min; the chloride ion content of the water is ≤500mg / L, pH 6.5-8.
5.
2. The concrete as described in claim 1, characterized in that: In the compounding process of the slow-release polycarboxylate superplasticizer, sodium pyrophosphate is added to the mother liquor in a mass ratio of 0.05-0.1 parts based on the mass of the mother liquor; the purity of sodium pyrophosphate is ≥98.0%, and the water-insoluble matter is ≤0.2%.
3. The concrete as described in claim 1 or 2, characterized in that: The finished slow-release polycarboxylate superplasticizer has a solid content of 40% ± 2%, a pH of 6.5-7.5, and a density of 1.05-1.10 g / cm³ at 20°C. 3 .
4. The concrete as described in claim 1, characterized in that: The molecular weight of polyethylene glycol monomethyl ether is 2000-2400, the purity is ≥99.5%, and the hydroxyl value is 23-28 mgKOH / g; the purity of acrylic acid is ≥99.0%, the moisture content is ≤0.2%, and the content of polymerization inhibitor is 200-300 ppm; the purity of itaconic acid monobutyl ester is ≥98.5%, the moisture content is ≤0.3%, and the double bond retention rate is ≥97%.
5. The concrete as described in claim 1, characterized in that: The purity of dimethyl carbonate modified acrylate is ≥98.0%, and the degree of hydrolysis is adjustable from 30% to 70%; the purity of N-hydroxymethylacrylimide is ≥97.5%, the moisture content is ≤0.5%, and the melting point is 75-78℃; the purity of L-aspartic acid dimethyl ester is ≥98.0%, and the moisture content is ≤0.5%.
6. A method for preparing concrete as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Preparation of slow-release polycarboxylate superplasticizer mother liquor: By mass, 80-90 parts of polyethylene glycol monomethyl ether, 25-30 parts of acrylic acid, 8-12 parts of itaconic acid monobutyl ester, 5-8 parts of dimethyl carbonate modified acrylate, 3-5 parts of N-hydroxymethylacrylimide, 1.2-1.8 parts of ammonium persulfate, 0.8-1.2 parts of mercaptoacetic acid and 150-180 parts of deionized water are mixed for polymerization reaction; (2) Compound water-reducing agent finished product: Based on the mass of the water-reducing agent mother liquor, add 0.5-1 parts by mass of L-aspartic acid dimethyl ester and 0.1-0.3 parts by mass of nano-calcium carbonate to the mother liquor obtained in step (1), and mix and disperse evenly; (3) Staged mixing: Add 60%-70% water to the mixture of sand and stone and stir for 0-30s. Add all the slow-release polycarboxylate superplasticizer and continue stirring for 30-60s. Then add cement and the remaining 30%-40% water and stir for 60-120s until uniform. The conductivity of the deionized water is ≤10μS / cm, pH is 6.5-7.5, and the total hardness is ≤50mg / L based on calcium carbonate.
7. The preparation method according to claim 6, characterized in that: The polymerization reaction in step (1) specifically includes: After drying polyethylene glycol monomethyl ether at 80℃ for 2 hours, it is added to a reactor with 80-90 parts of deionized water and heated to 75℃±1℃ for 30 minutes. Acrylic acid, itaconic acid monobutyl ester, dimethyl carbonate modified acrylate, and N-hydroxymethylacrylimide are mixed to prepare a premix, which is added dropwise to the reactor at a rate of 1.5-2.0 L / h for 3 hours±10 minutes. Ammonium persulfate and mercaptoacetic acid are dissolved in 30-40 parts of deionized water to prepare a mixture, which is added to the reactor in three portions: one-third at the beginning of the premix addition, one-third at 1.5 hours of addition, and one-third at the end of the addition. After the premix addition is completed, the temperature is raised to 85℃±1℃ and maintained for 2 hours. The mixture is then cooled to below 40℃ and filtered through a 100μm filter to obtain the water-reducing agent mother liquor.
8. The preparation method according to claim 6, characterized in that: The mixing and dispersion process in step (2) is as follows: First, stir at 1500 rpm for 5 minutes. Then, add L-aspartic acid dimethyl ester and nano-calcium carbonate. After each component is added, disperse at 2500 rpm for 15 minutes. Finally, add deionized water to adjust the solid content of the water-reducing agent to 40% ± 2%, the pH to 6.5-7.5, and the density at 20℃ to 1.05-1.10 g / cm³. 3 .
9. The preparation method according to claim 6, characterized in that: In the staged mixing of step (3), the mixing speed is 25 rpm for 0-30s and 30-60s, and 30 rpm for 60-120s; the concrete is discharged within 3 minutes after mixing is completed, and the discharge temperature is 15-25℃.
Citation Information
Patent Citations
Amino acid-modified mud-resistant polycarboxylic acid water reducing agent and preparation method thereof
CN110760037A
Anti-mud slow-release polycarboxylate superplasticizer as well as preparation method and application thereof
CN114213603A